2022
DOI: 10.3390/ijms23063408
|View full text |Cite
|
Sign up to set email alerts
|

Brain Cholesterol Biosynthetic Pathway Is Altered in a Preclinical Model of Fragile X Syndrome

Abstract: Fragile X Syndrome (FXS) is the most frequent form of inherited X-linked pathology, associated with an intellectual and developmental disability, and currently considered the first monogenic cause of autism spectrum disorder (ASD). Low levels of total cholesterol reported in the serum of FXS patients, and evidence that FMRP targets a subset of mRNAs encoding proteins of lipid synthesis and transport suggests that the cholesterol metabolism impairments could be involved in FXS. Thus, the aim of the presented wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…A major finding of this study was the dysregulated cholesterol biosynthesis in astrocytes derived from human FXS stem cells. Reduced cholesterol in serum and platelets of FXS patients (Berry‐Kravis et al, 2015; Caku et al, 2017) as well as in the serum of an FXS rat model (Parente et al, 2022) have previously been reported. Brain cholesterol metabolism is considered to be separated from the rest of the body because of the blood–brain barrier (Kong et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A major finding of this study was the dysregulated cholesterol biosynthesis in astrocytes derived from human FXS stem cells. Reduced cholesterol in serum and platelets of FXS patients (Berry‐Kravis et al, 2015; Caku et al, 2017) as well as in the serum of an FXS rat model (Parente et al, 2022) have previously been reported. Brain cholesterol metabolism is considered to be separated from the rest of the body because of the blood–brain barrier (Kong et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, the report of cholesterol levels in the brain of a rat FXS model has shown increased levels of cholesterol and only in a single brain region (Parente et al, 2022). In the adult brain, astrocytes are considered the main producers of cholesterol (Ho et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the results of contextual fear conditioning, amygdala levels of 24S-HC will be of interest to explore in future studies. Past work has demonstrated similar levels of CP46A1 and 24S-HC in the amygdala compared with the hippocampus [ 8 , 9 , 46 ], and most cells of the amygdala are VGLUT1 positive [ 47 ], suggesting that 24S-HC levels in the amygdala should be reduced in cKO mice. We also acknowledge that deletion in a subset of cells does not guarantee a loss of function in those cells, since 24S-HC is secreted and, thus, can potentially have non-cell autonomous effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still little knowledge in regard to brain cholesterol homeostasis in ASD. A recent study found that the FMR1 mouse model of autism displays differences in cholesterol receptor expression in the brain, with Low-density Lipoprotein Receptor expression increased specifically in the cortex 21 . This correlates well with our finding of increased cholesterol biosynthesis genes in the cortices of B. fragilis treated mice.…”
Section: Discussionmentioning
confidence: 99%